Uncovering Molecular Mechanisms of Feed Efficiency in Pigs Through Multi-Omics Analysis of the Jejunum - Saixian Zhang; Yue Xiang; Yaobang Jian; Qiulin Zhao; Jiahui Sun; Yi Huang; Jing Xu; Xiaolong Qi; Jingjin Li; Zhuqing Zheng; Liangliang Fu; Yuwen Liu; et al. (Animals, 2025)
Feed efficiency (FE) is a crucial trait in pig production that influences both economic viability and environmental sustainability. The jejunum, an essential organ for nutrient absorption, plays a significant role in determining FE by affecting how pigs process and utilize feed. To explore the genetic and regulatory mechanisms behind FE, we conducted an integrative multi-omics study using RNA sequencing (RNA-seq) and ATAC sequencing (ATAC-seq) on pigs with high and low FE. By comparing gene expression and chromatin accessibility profiles in the jejunum, we identified key differentially expressed genes (DEGs) and differentially accessible regions (DARs) associated with lipid metabolism and immune function, both of which are critical pathways for efficient growth. Notably, we identified transcription factors such as GATA4 and EHF and genes like SCARB1 and GRXCR1 that may play regulatory roles in FE. Our findings provide novel insights into the molecular mechanisms governing FE in pigs, offering potential targets for genetic selection and nutritional interventions to enhance feed efficiency and sustainability in pig production.